"Être avec (le) Christ ou vivre pour ses frères". L’exégèse de Philippiens 1, 23-24 aux xiie et xiiie siècles - Dahan, Gilbert (Revue d'études augustiniennes et patristiques, 2014)
Study of the commentaries on Philippians 1:23-24, of the 12th and 13th centuries. First, textual problems: in his De doctrina christiana, S. Augustine noticed some hesitation in the punctuation of v. 23, which appeared also frequently in the Middle Ages. Some variae lectiones and some notes on the vocabulary are also examined. Secondly, doctrinal study: three questions are asked: Why does the Apostle hesitate, how can he have “a desire to depart”, and what is the meaning of “to be with Christ”? In the appendice are given the texts of the commentaries of Raoul of Laon, Gilbert of la Porrée, Stephan Langton, and Nicholas of Gorran.